IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI (GAYA BELAJAR) PADA KELAS II MATA PELAJARAN MATEMATIKA - Salsa, Hanung Salsabila Pramesti; Noviana Dini Rahmawati; Khafidlotur Rofiqoh; Noor Miyono (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
Currently, Indonesian education is experiencing a slight decline after Covid-19. The aim of this study is to implementation learning style differentiation and analyze the effectiveness carried out in the learning process using mathematics subjects regarding Numbers Up to 10,000. This study was conducted using qualitative methods at SDN Sendangguwo 01 Semarang. The results of observations and diagnostic tests carried out, in the first table, 29% of students have an auditory learning style. Then 54% of students have a visual learning style and 17% of students have a kinesthetic learning style. From the results of the interviews given, it can be seen that differentiated learning using learning styles can increase students' interest in the teaching and learning process.